Management of Hydropower Tunnels to Prevent Collapse and Remedial Measures - Tun, Sein Win; Singal, Sunil Kumar (Hydro Nepal: Journal of Water, Energy and Environment, 2016)
Tunnels are important structures in hydropower projects as they reduce the length of the water conductor system. However, tunnels also pose the possibility of collapse during construction which may cause significant time and cost overruns. Moreover, collapsing tunnels pose threats to workers and machinery. Systematic control and understanding of tunnel physics is key to preventing these dangers. In this paper, we explore the most effective means for constructing tunnels for hydropower projects.HYDRO Nepal JournalJournal of Water, Energy and EnvironmentIssue: 19Page: 31-37